(NkLIMATOLOGIQ (B:s (Nu^EBNOE POSOBIE (B/s - (NdROZDOW(B, (NoLEG aLEKSEEWI^s; (NwASILXEW(B, (Nw(B.(Na(B.s; (NkOBY[EWA(B, (Nn(B.(Nw(B.s; (NdROZDOW(B, (NoLEG aLEKSEEWI^s; (NkOBY[EWA(B, (Nn(B.(Nw(B.s ((Nl(B. :s (NgIDROMETEOIZDAT(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 558-561s
(NpREDM(B. (NUKAZ(B.: (NS(B. 562-564s
Keywords: (NkLIMATOLOGIQs -- (Nu^EBNIKI I POSOBIQs